PDK1, associated with glycolytic metabolism, is a potential prognostic biomarker in osteosarcoma - Jin Qi; Sihang Liu; Xufeng Hu; Xikang Luo; Yapeng Wang (PLoS ONE, 2025)
The study explores the prognostic significance and therapeutic potential of 3-phosphoinositide dependent protein kinase-1 (PDK1) in osteosarcoma. Using bioinformatics analysis and experimental validation, we analyzed PDK1 expression and its correlation with patient prognosis from GEPIA and UCSCXena databases. High PDK1 expression was found to be significantly associated with reduced survival in osteosarcoma patients, suggesting its value as a prognostic biomarker. Functional assays were performed to investigate the biological processes influenced by PDK1. Gene Ontology (GO) analysis indicated that PDK1 is involved in metabolism and cell proliferation. KEGG enrichment analysis revealed that genes related to PDK1 are enriched in pathways associated with metabolism, cell proliferation, and immune escape. In vitro experiments demonstrate that silencing PDK1 impairs glycolysis, reduces proliferation, and induces apoptosis in 143B osteosarcoma cells. Pan-cancer analysis confirms PDK1’s overexpression and poor prognosis association in multiple malignancies. Pan-cancer analysis extended the findings to other cancer types, confirming that PDK1 is overexpressed in multiple malignancies and generally associated with poor prognosis. This reinforces the potential of PDK1 as a universal biomarker and therapeutic target in oncology. The findings suggest PDK1 as a critical regulator of glycolytic metabolism and a potential therapeutic target in osteosarcoma. Targeting PDK1 could provide a novel therapeutic strategy for treating osteosarcoma and possibly other cancers.